Odpowiedzi

  • Użytkownik Zadane
2010-02-24T17:57:55+01:00
27.
a) abc-(abc-(-xyz-(xyz-abc)))=abc-(abc-(-xyz-xyz+abc))=abc-(abc+2xyz-abc)=abc-2xyz
b)s²t-(st²-(s²t-(st²-s²t)))=s²t-(st²-(s²t-st²+s²t))=s²t-(st²+st²-2s²t)=s²t+2s²t-2st²=3s²t+2st²=st(3s+2t)
c)x²yz-(xy²z-(xyz²-(x²yz-xy²z)))=x²yz-(xy²z-(xyz²-x²yz+xy²z)=x²yz-(xy²z-xyz²+x²yz-xy²z)=x²yz+xyz²-x²yz=xyz²
Najlepsza Odpowiedź!
2010-02-24T17:58:14+01:00
Opuszczasz nawiasy zmienisz znaki i w a bd -2xyz+abc
w b 3skwadratt -2stkwadrat
w c 2xkwadratyz + xyz kwadrat